Project methods as an effective means of organization of educational work in the classroom for Russian language in higher institutions. (Eurasian Journal of Philology Science and Education, 2015)
This article is devoted to a comprehensive analysis of modern educational technologies, in particular, project technologies that meet today’s educational process of higher education. The article states that when teaching Russian as a non-native language, we can use the method of projects. The implementation of the principles of constructing the project method in teaching the Russian language will form highly developed individuals, bilingual and polylingual, with multilingual and multicultural competences.The author describes in detail the consecutive stages of project method and highlights the issues related to the role of this technology in the educational process. In conclusion, the article resumes that the application of this method will help university instructors to solve didactic problems of teaching the Russian language in the general system of communicativelydirectedand professionally-directed training of future specialists.
Keywords: project; motivation; project-based learning; project-based technology; organization of the educational process; project activity; an effective means of teaching the Russian language; innovative technology; professionally-directed learning